Sodium citrate pretreatment enhances CAR-T cell persistence and anti-tumor efficacy through inhibition of calcium signaling - Yin, Xuechen; Chen, Wenwen; Ao, Xudong; Xu, Luxia; Cao, Jiujiu; Huang, Tinghui; Liang, Junqing; Hu, Jianhua; Liu, Jiaqi; Wang, Xinping; Li, Wenying; Zhou, Muya; et al. (Frontiers in Immunology, 2025)
IntroductionChimeric antigen receptor T cell (CAR-T) therapy has shown success in treating hematological malignancies, but its effectiveness against solid tumors is hindered by T cell exhaustion. During in vitro expansion, tonic signaling induced by CAR expression contributes to CAR-T cell exhaustion, which can be mitigated by inhibiting calcium signaling. Given that sodium citrate can chelate calcium ions and inhibit calcium signaling, in this study, we investigated whether sodium citrate could reduce exhaustion and enhance CAR-T cell function.MethodsWe constructed anti-CD70 CAR-T cells and cultured them in the presence of sodium citrate. The characteristics and functionality of sodium citrate-pretreated CAR-T cells were assessed through in vitro and in vivo experiments. To further validate our observation, we also treated anti-mesothelin (MSLN) CAR-T cells with sodium citrate and detected the phenotypes and anti-tumor function of CAR-T cells.ResultsWe found that sodium citrate-pretreated anti-CD70 CAR-T cells exhibited reduced exhaustion, increased memory T cell proportions, and enhanced anti-tumor efficacy both in vitro and in vivo. Notably, sodium citrate treatment improved the in vivo persistence of CAR-T cells and prevented tumor recurrence. These beneficial effects were also observed in anti-MSLN CAR-T cells. Transcriptomic and metabolite analyses revealed that sodium citrate inhibited calcium signaling, mTORC1 activity, and glycolysis pathways, thus modulating T cell exhaustion and differentiation.DiscussionOur findings suggest that sodium citrate supplementation during CAR-T cell expansion could be a promising strategy to improve CAR-T therapy for solid tumors by preventing exhaustion and promoting memory T cell formation.